2018
DOI: 10.1186/s12968-018-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the cone operation on left ventricular size, function, and dyssynchrony in Ebstein anomaly: a cardiovascular magnetic resonance study

Abstract: BackgroundIn addition to tricuspid regurgitation (TR) and right ventricular (RV) enlargement, patients with Ebstein anomaly are at risk for left ventricular (LV) dysfunction and dyssynchrony. We studied the impact of the cone tricuspid valve reconstruction operation on LV size, function, and dyssynchrony.MethodsAll Ebstein anomaly patients who had both pre- and postoperative cardiovascular magnetic resonance (CMR) studies were retrospectively identified. From cine images, RV and LV volumes and ejection fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
4
18
0
1
Order By: Relevance
“…In unrepaired Ebstein’s anomaly, CMR assessment of the abnormal tricuspid valve leaflets, tricuspid regurgitation, and RV volumes and function can be used to determine the suitability for operative repair [ 37 , 38 ] and predict major adverse cardiac events and atrial arrhythmia [ 39 ]. Following repair, CMR can demonstrate the extent of ventricular remodeling [ 40 , 41 ].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…In unrepaired Ebstein’s anomaly, CMR assessment of the abnormal tricuspid valve leaflets, tricuspid regurgitation, and RV volumes and function can be used to determine the suitability for operative repair [ 37 , 38 ] and predict major adverse cardiac events and atrial arrhythmia [ 39 ]. Following repair, CMR can demonstrate the extent of ventricular remodeling [ 40 , 41 ].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Cone reconstruction can reduce both tricuspid regurgitation and right ventricular end‐diastolic volume. Moreover, it can reduce right ventricular stroke volume without reducing the right ventricular ejection fraction, while left ventricular end‐diastolic volume and left ventricular stroke volume can be increased 8 . Both the short‐ and long‐term prognoses are satisfactory 7,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging outcomes were reported by other studies performing CR [14,15] . Beroukhim et al [16] also reported improvements in RV volume and TR, besides improvement in left ventricular systolic function and synchrony in patients who underwent CR [17] .…”
Section: Discussionmentioning
confidence: 99%